2019
DOI: 10.1107/s2053230x19007209
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the allosteric site of human liver pyruvate kinase upon activator binding include the breakage of an intersubunit cation–π bond

Abstract: Edited by R. J. Read, University of Cambridge, England Keywords: pyruvate kinase; allosterism; human liver isozyme. PDB references: human liver pyruvate kinase, D499N variant, 6nn4; W527H variant, 6nn5; Á529/S531G variant, 6nn7; S531E variant, 6nn8Supporting information: this article has supporting information at journals.iucr.org/f Human liver pyruvate kinase (hLPYK) converts phosphoenolpyruvate to pyruvate in the final step of glycolysis. hLPYK is allosterically activated by fructose-1,6-bisphosphate (Fru-1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…By having a method that reports on many functions at once, we have found hLPYK to be a useful model to evaluate individual amino acid positions based on functional outcomes due to substitution 2,3 . In particular, our past studies have identified substitutions at nonconserved positions in and near the allosteric binding sites that modulated multiple functional parameters 2,3,5‐9 (Figure 1, green dots).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By having a method that reports on many functions at once, we have found hLPYK to be a useful model to evaluate individual amino acid positions based on functional outcomes due to substitution 2,3 . In particular, our past studies have identified substitutions at nonconserved positions in and near the allosteric binding sites that modulated multiple functional parameters 2,3,5‐9 (Figure 1, green dots).…”
Section: Resultsmentioning
confidence: 99%
“…We have been using human liver pyruvate kinase (hLPYK) to probe the functional roles of nonconserved protein positions. In our studies, substitutions at nonconserved positions in and near the allosteric binding sites modulated multiple functional parameters 2,3,5‐9 . To better understand how the nonconserved positions contribute to function, we wish to compare their biochemical, biophysical and structural characteristics to those of nonconserved positions that have little effect on function.…”
Section: Introductionmentioning
confidence: 99%
“…The L and R isozymes are dominant in the liver and erythrocytes respectively, and both forms are allosterically regulated by FBP. Recently, in human liver PyK switching of the allosteric loop from an open to closed conformation in the presence of FBP has been attributed to the change in interactions at the C–C interface which leads to the altered substrate affinity of the enzyme . Muscle specific isoforms, PyK‐M1 and PyK‐M2, are expressed from the same gene but differ in 22 residues located within a 56 residue region situated at the C–C interface close to the allosteric effector‐binding site.…”
Section: Structurally and Functionally Distinct Pyksmentioning
confidence: 99%
“…Recently, in human liver PyK switching of the allosteric loop from an open to closed conformation in the presence of FBP has been attributed to the change in interactions at the C-C interface which leads to the altered substrate affinity of the enzyme. 76 Muscle specific isoforms, PyK-M1 and PyK-M2, are expressed from the same gene but differ in 22 residues located within a 56 residue region situated at the C-C interface close to the allosteric effectorbinding site. PyK-M1 is a highly active nonallosteric form found in tissues, such as heart, brain, and skeletal muscle that need to rapidly generate large amounts of ATP.…”
Section: Vertebrate Pyk Isozymesmentioning
confidence: 99%
“…To support this idea, first consider that many pyruvate kinase isozymes are regulated by phosphorylated sugars (55), although the identity of those effectors varies considerably among isozymes (56). Our previous study used extensive numbers of effector analogs, point mutations, and crystallographically determined structures to characterize which regions of the fructose-1,6-bisphosphate (Fru-1,6-BP) allosteric site of human liver PYK (LPYK) contribute to allostery (50,57). One of the two PYK isozymes from Escherichia coli (EcPYK) is also regulated by Fru-1,6-BP (58).…”
Section: The Influence Of Silent Coupling On the Evolution Of An Allo...mentioning
confidence: 99%